2020
DOI: 10.33533/jpm.v14i1.1597
|View full text |Cite
|
Sign up to set email alerts
|

The risk of smoking with stroke in Asia : meta-analysis

Abstract: This study uses a systematic method of review and meta-analysis to look at the risk of smoking with stroke in Asia. Further analysis based on the stroke subtype (ischemic stroke and haemorrhagic stroke was also carried out. Literature search was carried out in the PubMed, EBSCO and Google Scholar databases. Q tests were performed to determine the heterogeneity of included studies. Funnel plot, Egger regression test and trim and fill methods were used to identified publication bias and with the transformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Merokok dapat meningkatkan risiko stroke, Penyebab stroke pada perokok dapat dipicu oleh asap rokok yang mengandung lebih dari 7.000 bahan kimia beracun, bahan kimia ini akan mengubah dan merusak sel-sel diseluruh tubuh, perubahan yang disebabkan oleh bahan kimia ini meningkatkan risiko stroke pada perokok,adapun mekanisme perokok dapat menyebabkan stroke yaitu penurunan aliran darak keotak sehingga menyebabkan vasokontriksi yang memepercepat terjadinya trombus, merokok juga dapat menurunkan HDL dan merusak sel endotel yang menyebabkan ateroma. (Hasnah, Lestari, & Abdiana, 2020). Faktor risiko yang dapat mempengaruhi kejadian stroke yaitu merokok yang dapat menyebabkan perdarahan intraserebral dengan merusak dinding arteri yang pecahnya pembuluh darah.…”
Section: Hasil Dan Pembahasanunclassified
“…Merokok dapat meningkatkan risiko stroke, Penyebab stroke pada perokok dapat dipicu oleh asap rokok yang mengandung lebih dari 7.000 bahan kimia beracun, bahan kimia ini akan mengubah dan merusak sel-sel diseluruh tubuh, perubahan yang disebabkan oleh bahan kimia ini meningkatkan risiko stroke pada perokok,adapun mekanisme perokok dapat menyebabkan stroke yaitu penurunan aliran darak keotak sehingga menyebabkan vasokontriksi yang memepercepat terjadinya trombus, merokok juga dapat menurunkan HDL dan merusak sel endotel yang menyebabkan ateroma. (Hasnah, Lestari, & Abdiana, 2020). Faktor risiko yang dapat mempengaruhi kejadian stroke yaitu merokok yang dapat menyebabkan perdarahan intraserebral dengan merusak dinding arteri yang pecahnya pembuluh darah.…”
Section: Hasil Dan Pembahasanunclassified
“…An analysis by stroke subtype showed that smokers were 2.30 times more likely to have an ischemic stroke than non-smokers and 2.77 times more likely to have a hemorrhagic stroke than non-smokers. Hemorrhagic stroke is bleeding within the brain, and ischemic stroke is caused by the buildup of fatty deposits on the inner lining of blood vessels (Hasnah et al, 2020).…”
Section: Impact Of Smoking On Healthmentioning
confidence: 99%